OBSERVATIONS ON THE FINE STRUCTURE OF LUTEIN CELLS - Enders, Allen C. (The Rockefeller University Press, 1962)
Corpora lutea from the period of delayed implantation and from early postimplantation stages of the armadillo, mink, and rat were fixed in buffered osmium tetroxide-sucrose or potassium permanganate. After rapid dehydration, the portions of the corpora lutea were embedded in either methacrylate or epoxy resin. Examination of the lutein cells by electron microscopy revealed the presence, in the better preserved material, of an extensive development of tubular agranular endoplasmic reticulum. Although the membranes of the endoplasmic reticulum are the most striking feature of the lutein cells of both stages of the three animals examined, very numerous large mitochondria with cristae that exhibit a variety of forms tending toward villiform, and protrusions and foldings of the lutein cell margins on the pericapillary space are also characteristic of these cells. Certain minor differences in the lutein cells of the species examined are also noted. No indications of conversion of mitochondria into lipid, of accumulation of lipid in the Golgi area, or of the protrusion of lutein cells into spaces between the endothelial cells, as suggested by other authors, were noted in these preparations. Some of the difficulties inherent in the visualization of the secretory activity of cells producing steroid hormones are briefly discussed.